Hypomethylating Agent-Based Combination Therapies to Treat Post-Hematopoietic Stem Cell Transplant Relapse of Acute Myeloid Leukemia - Ciotti, Giulia; Marconi, Giovanni; Martinelli, Giovanni (Frontiers in Oncology, 2022)
Allogeneic stem cell transplantation still represents the best curative option for most patients with acute myeloid leukemia, but relapse is still dramatically high. Due to their immunologic activity and safety profile, hypomethylating agents (HMAs) represent an interesting backbone for combination therapies. This review reports mechanism of action, safety, and efficacy data on combination strategies based on HMAs in the setting of post-allogeneic stem cell transplant relapse. Several studies highlighted how HMAs and donor lymphocyte infusion (DLI) combination may be advantageous. The combination strategy of HMA with venetoclax, possibly in association with DLI, is showing excellent results in terms of response rate, including molecular responses. Lenalidomide, despite its well-known high rates of severe graft-versus-host disease in post-transplant settings, is showing an acceptable safety profile in association with HMAs with a competitive response rate. Regarding FLT3 internal tandem duplication (ITD) mutant AML, tyrosine kinase inhibitors and particularly sorafenib have promising results as monotherapy and in combination with HMAs. Conversely, combination strategies with gemtuzumab ozogamicin or immune checkpoint inhibitors did not show competitive response rates and seem to be currently less attractive strategies. Associations with histone deacetylase inhibitors and isocitrate dehydrogenase 1 and 2 (IDH1/2) inhibitors represent new possible strategies that need to be better investigated.